Interferon-γ-induced GBP1 is an inhibitor of human papillomavirus 18 - Min Xu; Miao-Chun Lin; Zhao-Hui Li (BMC Women's Health, 2024)
Abstract Background Human papillomavirus (HPV) infection is an important factor leading to cervical cell abnormalities. 90% of cervical cancers are closely associated with persistent infection of high-risk HPV, with the highest correlation with HPV16 and 18. Currently available vaccines and antivirals have limited effectiveness and coverage. Guanylate binding protein 1 (GBP1) was induced by interferon gamma and involved in many important cellular processes such as clearance of various microbial pathogens. However, whether GBP1 can inhibit human papillomavirus infection is unclear. Results In this study, we found that GBP1 can effectively degrade HPV18 E6, possibly through its GTPase activity or other pathways, and E6 protein degrades GBP1 through the ubiquitin-proteasome pathway to achieve immune escape. Conclusion Therefore, GBP1 is an effector of IFN-γ anti-HPV activity. Our findings provided new insights into the treatment of HPV 18 infections.